Extended HPV genotyping by the BD Onclarity assay: concordance with screening HPV-DNA assays, triage biomarkers, and histopathology in women from the NTCC2 study - Laura De Marco; Simonetta Bisanzi; Guglielmo Ronco; Pamela Mancuso; Francesca Carozzi; Elena Allia; Raffaella Rizzolo; Daniela Gustinucci; Helena Frayle; Jessica Viti; Anna Iossa; Elena Cesarini; et al. (Microbiology Spectrum)
ABSTRACT The use of clinically validated human papillomavirus (HPV) assays is recommended in cervical cancer screening, and extended genotyping is getting attention as a triage biomarker because of the different oncogenic risk of the high-risk HPV genotypes. We compared the results of the Becton & Dickinson (BD) Onclarity HPV assay, on the residual baseline cervico-vaginal specimens of the NTCC2 trial, to those of the screening HPV-DNA assay (Cobas 4800 or HC2) and to cytology, p16/ki67 and E6/E7 mRNA triage results. We genotyped virtually all HPV-positive women and a consecutive sample of HPV-negatives. Among the 3,129 baseline-positives, 75.5% (k = 0.368) were BD-positive, as were 5 of the 333 baseline-negatives (1.5%). The concordance between BD and HPV-DNA screening test was 87% for Cobas (1,250/1,436) and 65.9% for HC2 (1,115/1,693). A higher than the recommended positivity threshold for Onclarity would increase the agreement but would not improve concordance in the overall screening population. Among the baseline-positive cases, we observed an increasing trend of BD positivity with cytology severity (from 71.6% in negative for intraepithelial lesion of malignancy to 95.1% in ASC-H+ samples), with histologically confirmed CIN3 (96.9%), with p16/ki67 dual staining positivity (90.9% among the positive and 69.6% among the negative specimens), and with E6/E7 mRNA positivity (93.4% in the mRNA-positive cases vs 39.7% among the mRNA-negatives). Our findings confirm some disagreement among different HPV assays used for screening. Nevertheless, the agreement is substantial for women with high-grade cytology, histologically confirmed CIN3, and p16/ki67 or mRNA positivity at triage, thus confirming a good clinical performance of all the tests used.The NTCC2 trial is registered as Clinicaltrials.gov identifier NCT01837693.IMPORTANCELarge randomized clinical trials have demonstrated that human papillomavirus (HPV) testing for high-risk types is more effective than cytology in detecting pre-cancerous lesions and preventing cervical cancer. Its use is being implemented in cervical cancer screening in several countries. The most recent guidelines recommend a risk-based management. It is therefore important to assess the individual risk of having/developing high-grade lesions of women testing high-risk HPV-positive. A crucial viral factor influencing the risk is the HPV genotype since different types are associated to different carcinogenetic risks. Understanding the degree of concordance among different assays targeting either HPV presence/type(s) or cellular morphology and proteins’ expression provides knowledge useful to better define how these tests can be used in screening protocols for an effective triage and to anticipate the possible implementation issues. Our study shows that the concordance between tests is higher when the infections have a higher probability of producing a clinically relevant lesion.